Public Investment and Growth in the Eastern Caribbean - Roache, Shaun (IMF Working Papers; Working Paper ;, 2007)
This paper quantifies the effect of public investment on growth in the ECCU. The results, emerging from panel vector autoregressions, indicate that the return on public investment, as defined by Perreira (2000), is very likely negative. This means that the total change in real output induced by one EC dollar of public investment, due to its short-run impact on demand, or the longer-run impact on supply, is below one EC dollar. Public investment shocks also appear to appreciate the real exchange rate, suggesting that the short-run demand impact is larger than the long-run supply response.